Challenges in culturing macaca fascicularisBone marrow stem cells - Sharen, S@Sharen Aini; Masfueh, R; Badiah, B; Ng, M.H; Shamsul, B.S; Chua, K.H; Low, C.K; Mohd Nazimi, A.J; Rifqah, N; Norziha, Y; Shariffah Shuriana, A.S; Ruszymah, B.H.I; et al. (Universiti Kebangsaan Malaysia, 2012)
Culturing Macaca fascicularis bone marrow stem cells in fetal bovine serum (FBS) resulted in low proliferation and long period of incubation. Therefore, its potential uses are exhausted. Here we report the establishment of culturing the Macaca fascicularis bone marrow stem cells using the FBS in combination with autologous serum. Five percent autologous serum was added to the Minimum Essential Medium (MEM) alpha medium and 10% FBS while 0.2 mM acid ascorbic 2-phosphate, 10 mM β-glycerolphosphate, 10-8 molar dexamethasone were used for osteogenic induction. Following this combination, our results showed higher growth kinetic i.e. 1.41% growth rate higher compared to only 0.46% growth rates of the cells using FBS alone and shorter population doubling time (4 to 7 days) compared to the culture without the combination of FBS and autologous serum (30 days). Thus, the combination of the FBS and autologous serum permits fast cell growth and tissue construction.